Utilization and outcomes of a Whole Health model of care by Veterans with psychiatric illness - W.R. Marchand; Chong Zhang; Clayton Hamilton; Angela P. Presson; Richard Nelson; Minkyoung Yoo; Eric L. Garland; Elena Nazarenko; Tracy Herrmann (Elsevier, 2022)
Objectives: The Veterans Health Administration (VHA) is implementing a model of healthcare known as Whole Health (WH). The goal of WH is to shift from a disease-oriented system to one that emphasizes health promotion and disease prevention as well as promotes the use of Complementary and Integrative Health. The aim of this project was to investigate utilization and outcomes of WH programming among Veterans with psychiatric disorders. Design: This was a retrospective study. Subjects were 7138 Veterans who had a mental health diagnosis. Descriptive data, as well as within- and between-subjects analyses were conducted to investigate utilization and outcomes. Setting: The study was conducted at a large VHA medical center. Interventions: Whole health interventions considered in this study were mindfulness training, health education, wellbeing, and nutrition classes as well as health coaching. Other whole health interventions, such as acupuncture and message were not evaluated. Main outcome measures: Utilization of mental health treatment services, medication prescriptions, pain scores and suicide-related behaviors were the primary outcome measures. Results: There were 305 Veterans with at least one WH appointment. The existence of several specific psychiatric disorders was associated with WH utilization. The mean number of appointments completed per individual was 6.9 for all WH programming. Finally, WH participation was associated with decreased risk of suicide as well as reduced use of mental health services. There were no significant changes to other outcome variables. Conclusions: WH programming shows promise to reduce suicide risk and the need for mental health services among this population. Additionally, WH services were underutilized and there was a lack of treatment engagement.